Effect of the addition of cactus (O. ficus-indica) to the lactating sows’ diet on piglet development at lactation and post-weaning - Ortiz, Ruy; Orozco, Alejandro; Ordaz, Gerardo; López, Manuel; Pérez, Rosa Elena (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The aim was to evaluate the effect of cactus (Opuntia ficus-indica) to the lactating sows’ diet on piglet development at lactation and post-weaning. Materials and Methods: Twenty-four litters of hybrids sows were evaluated in this study. The sows were divided into two groups: Control (CG), sows fed conventionally and experimental (EG), sows fed with commercial fed plus cactus. Post-weaning, the piglets of both groups were monitored up to the 20 kg liveweight (LW). It was evaluated, lactation (in sows): feed intake (FI), milk production (MP), and quality (MQ) and LW of the piglet. Post-weaning (in piglets): FI, LW, and length of intestinal villi (LIV) at 0, 24 h, and 42 days post-weaning. Results: FI sow-1 was higher in EG (p < 0.05). MP, MQ, and LW piglet-1 at weaning were equal (p > 0.05). FI piglet-1 in the sixth and eighth week of age was higher in EG (p < 0.05); at the end of weaning phase, EG presented higher LW (p < 0.05): 8.4% more. LIV of the jejunum were higher (p < 0.05) in EG at 48 h (28.8%) and 42 days post-weaning (29.9%). At day 0, post-weaning LIV of the descending portion was higher (p < 0.05) in CG (1,571.0 μm) versus EG (1,058.0 μm). At day 42, post-weaning LIV of the transverse portion was higher (p < 0.05) in EG: 23.7% higher. Conclusion: Cactus intake in lactating sows does not affect the piglet development. However, post-weaning piglets present higher LIV in jejunum and transverse portion, aspect that improves LW. J. Adv. Vet. Anim. Res., 6(3): 290-299, September 2019